Integration of biotechnology and Islamic theological studies in Malaysia - Norazmi, Anas; Engku Ahmad Zaki, Engku Alwi; Mohd Hudzari, Razali; Zuriani, Yaacob; Zarinatun Ilyani, Abdul Rahman (IDOSI Publications, 2015)
Usuluddin is a branch of Islamic studies debating almost all pertinent issues related to basic beliefs of Muslims (aqeedah). This further embodies other main Islamic theological issues such as the divine (ilahiyat), propethood (nubuwwat), morality and manners (akhlaq) as well as the unseen (sam’iyyat) i.e. something that we have heard about but beyond human perception. To put this into perspective, the integration of two significant elements i.e. aqeedah and akhlaq obviously has great consequences particularly in pursuing modern biotechnological researches which should be based on Islamic laws and teachings. The relation between the two is the core to every human’s action and is adopted as a point of reference in man’s decision making processes. Hence, this paper hopes to highlight and discover the suitability and appropriateness of Islamic Studies courses integrated in biotechnology as offered at a number of Malaysian public universities these days. It is evident from the findings that University of Malaya (UM) offers eleven such courses as compared to Islamic Science University of Malaysia (USIM) as well as UniSZA (University of Sultan Zainal Abidin) with five and three courses respectively.The researchers employed qualitative method which mostly involved content analysis in order to gather related data. This idea suggests that the Usuluddin courses as offered by UM are more flexible in the sense that they provide more opportunities particularly in pursuing biotechnological research and joint research possibilities.